LEKSIKOGRAFI KAMUS DWIBAHASA PRANCIS-INDONESIA KHUSUS BIDANG BISNIS - Adisti Dwi Utami; Tri Indri Hardini; Yuliarti Mutiarsih (Linguistik Indonesia, 2019)
This research aims to describe lexicography in a French-Indonesian bilingual business dictionary that has been created and is available on dictionnaire-desaffaires.online. This research applies a descriptive qualitative method. The data collecting technique used in this research are questionnaire and lexicographic stages. The questionnaire is filled by Departement of French Language’s students of Universitas Pendidikan Indonesia who learn French Business course (Français des Affaires). It aims to find out their needs for business dictionary. The result shows that they need a business dictionary in French-Indonesian and they prioritize content and information structure. Moreover, the researcher will describe lexicography in this dictionary, namely the stages of its preparation and the content of the dictionary, which is macrostructure and microstructure. The macrostructure is arranged alphabetically, while the microstructure consists of definition and grammatical information. The grammatical information contained in this dictionary is four major word classes: nouns, verbs, adjectives and adverbs. It can be concluded that the needs of students for business-specific dictionary can be fulfilled by compiling a dictionary using lexicography.